THE IMPACT OF TSMC’S ESTABLISHMENT IN TAIBAO, CHIAYI ON LOCAL SMALL-SCALE DEVELOPERS: CHALLENGES AND STRAGEGIC RESPONSES - Huang, Kan-Chung; Hung, Yu-Ting; Chang, Yao-Lin; Chiu, Hsing-Chiao; Yang, Chien-Chung (International Journal of Application on Economics and Business, 2025)
This study focuses on Chiayi County and explores the effects of TSMC’s factory establishment on the housing market in Chiayi’s core area and examines the land acquisition and marketing strategies adopted by local small-scale developers in response. Following TSMC's announcement to set up a plant, the local government actively promoted public construction and infrastructure upgrades— enhancing roads, school districts, and overall living amenities—which gradually transformed Chiayi County into a region with growing development potential, stimulating both housing demand and supply momentum. First, this study reviews the literature to explore how TSMC's presence influences regional housing prices, land use, and residential supply. Then, it analyzes the characteristics of new housing projects in recent years, including the number of projects, floor area planning, building types, and developers’ marketing focuses. To gain deeper insight into the current market and developer strategies, the study builds on the above findings and adopts a qualitative approach, interviewing six professionals—including architects, appraisers, developers, and scholars—to analyze the current state and future trends of the local housing market from multiple expert perspectives. Key findings; (1) Although TSMC brings short-term excitement, most interviewees believe more attention should be paid to the actual inflow of workers and the diverse housing needs that follow—particularly regarding expectations for housing types, quality of life, and price affordability; (2) The influx of large developers from outside the region has driven up land and housing prices in Chiayi’s core areas, posing significant challenges for local developers in land acquisition and project launching. Moreover, current residential products lack differentiation and unique features, especially in the apartment market, where many projects heavily emphasize "smart homes" and "living convenience," resulting in market saturation and fatigue; (3) In terms of strategic responses, local developers must establish new market segmentation, target customer groups, and product positioning. Three strategic recommendations are proposed: (a) Segment the market based on home-buying purposes and lifestyles—such as first-time buyers, upgraders, tech professionals, and investors: (b) Offer differentiated products for each group, such as affordable high-function homes, medium-to-large smart homes, or compact units with rental potential for budget-conscious buyers; (c) Strengthen brand identity by aligning product positioning with different customer appeals—such as convenience, brand trust, investment value, and regional identity.